2018
DOI: 10.1016/j.ymeth.2018.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Implementing fast photochemical oxidation of proteins (FPOP) as a footprinting approach to solve diverse problems in structural biology

Abstract: Fast photochemical oxidation of proteins (FPOP) is a footprinting technique used in mass spectrometry-based structural proteomics. It has been applied to solve a variety of problems in different areas of biology. A FPOP platform requires a laser, optics, and sample flow path properly assembled to enable fast footprinting. Sample preparation, buffer conditions, and reagent concentrations are essential to obtain reasonable oxidations on proteins. FPOP samples can be analyzed by LC-MS methods to measure the modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 58 publications
1
36
0
Order By: Relevance
“…The area of incidence between the laser light and the sample is considerably larger for microtiter single pulse photolysis. The use of cylindrical lenses to asymmetrically compress the beam to the shape of the capillary allows traditional FPOP to reach higher laser fluences at more modest pulse energies [27] . Since the area illuminated is much larger in the microtiter plate, the laser energy per pulse required is considerably higher, potentially requiring a higher power laser.…”
Section: Resultsmentioning
confidence: 99%
“…The area of incidence between the laser light and the sample is considerably larger for microtiter single pulse photolysis. The use of cylindrical lenses to asymmetrically compress the beam to the shape of the capillary allows traditional FPOP to reach higher laser fluences at more modest pulse energies [27] . Since the area illuminated is much larger in the microtiter plate, the laser energy per pulse required is considerably higher, potentially requiring a higher power laser.…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrated that this normalization allows us to obtain identical footprints for proteins in widely differing scavenging backgrounds, which is key for comparability studies. Incorporation of a pinhole aperture as previously reported 36 allows for investigators to change fluence (and, therefore, the amount of radicals generated) without need of correcting for altered beam area by changing the flow rate.…”
Section: Resultsmentioning
confidence: 99%
“…buffer, ligand, detergent, lipids, excipients, allosteric modulator, etc.) 23,36 and isotope dilution GC-MS 37 . Perhaps the simplest was to replace a portion of the glutamine radical scavenger with adenine, which has an almost identical rate of reaction as glutamine 38 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fast photochemical oxidation of proteins (FPOP), a method that generates hydroxyl radicals by UV laser-induced photolysis of hydrogen peroxide, has demonstrated the ability to react with a wide variety of amino acids on the surface of the proteins and label them without altering the native protein structure during labeling [7][8][9]. FPOP coupled with MS has been rapidly adopted to protein structural biology research in recent decades [7,[10][11][12]. However, FPOP coupled with MS for membrane protein analysis remains limited, in part due to the low extent of labeling that has been reported.…”
Section: Introductionmentioning
confidence: 99%